1997
DOI: 10.1128/jb.179.18.5720-5727.1997
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory and photosensory perception in purple photosynthetic bacteria utilize common signal transduction components

Abstract: The chemotaxis gene cluster from the photosynthetic bacterium Rhodospirillum centenum contains five open reading frames (ORFs) that have significant sequence homology to chemotaxis genes from other bacteria. To elucidate the functions of each ORF, we have made various mutations in the gene cluster and analyzed their phenotypic defects. Deletion of the entire che operon (⌬che), as well as nonpolar disruptions of cheAY, cheW, and cheR, resulted in a smooth-swimming phenotype, whereas disruption of cheB resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 38 publications
6
62
0
Order By: Relevance
“…Indeed, half of the amino acid substitutions involve alterations in hydrophobicity or charge. Taken together with the results of our mutational analyses (17), these results indicate that the CheY domain of CheAY and CheY must serve distinct roles in chemotactic signal transduction in R. centenum.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Indeed, half of the amino acid substitutions involve alterations in hydrophobicity or charge. Taken together with the results of our mutational analyses (17), these results indicate that the CheY domain of CheAY and CheY must serve distinct roles in chemotactic signal transduction in R. centenum.…”
Section: Discussionmentioning
confidence: 50%
“…Mutational analysis has demonstrated that FrzE is involved in controlling the gliding reversal frequency (24). Similar analysis of R. centenum indicates that CheAY is involved in controlling the tumbling frequency, thereby indicating that CheAY and FrzE may have comparable functions (17).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Escherichia coli strain S17-1 ( pir)/pZJD17 was used for conjugation and transposition of the mini-Tn5 interposon (11). pZJD17 is derived from the previously described plasmid pUTmini-Tn5-Sm/Sp (15) with the 5Ј-and 3Ј-terminator sites deleted to decrease polarity effects caused by premature termination of transcription of downstream genes (10). Plasmid pSK(ϩ) (Bluescript; Stratagene) and E. coli strain DH5␣ were used for cloning and maintaining R. centenum chromosomal DNA fragments.…”
Section: Methodsmentioning
confidence: 99%